Association between prenatal exposure to multiple insecticides and child body weight and body composition in the VHEMBE South African birth cohort. (April 2018) - Coker, Eric; Chevrier, Jonathan; Rauch, Stephen; Bradman, Asa; Obida, Muvhulawa; Crause, Madelein; Bornman, Riana; Eskenazi, Brenda
Abstract: Background: Pregnant women may be co-exposed to multiple insecticides in regions where both pyrethroids and dichlorodiphenyltrichloroethane (DDT) are used for indoor residual spraying (IRS) for malaria control. Despite the potential for adverse effects on offspring, there are few studies in areas where IRS is currently used and little is known about the effects of pyrethroids on children's health. Methods: We investigated the relationship between concentrations of four urinary pyrethroid metabolites in urine and organochlorine pesticide concentrations in maternal blood collected near delivery on body weight and body composition among children ≤2 years old participating in the prospective South Africa VHEMBE birth cohort (N = 708). We used measurements of length/height and weight collected at 1 and 2 years of age to calculate body mass index (BMI)-for-age, weight-for-age, and weight-for-height z-scores based on World Health Organization standards. We fit separate single-pollutant mixed effects models for each exposure of interest and also stratified by sex. We also fit all analyte concentrations jointly by using a Bayesian kernel machine regression (BKMR) statistical method to assess variable importance of each analyte and to explore the potential for joint effects of the multiple exposures. Results: Single-pollutant linear mixed effects models showed that, among girls only, p, p ′-DDT was associated with higher BMI-for-age (adjusted [a]β = 0.22 [95% CI: 0.10, 0.35]; sex interaction p-value = 0.001), weight-for-height (aβ = 0.22 [95% CI: 0.09, 0.34]; sex interaction p-value = 0.002), and weight-for-age (aβ = 0.17 [95% CI: 0.05, 0.29], sex interaction p-value = 0.01). Although single-pollutant models suggested that p, p ′-DDT and dichlorodiphenyldichloroethylene ( p, p ′-DDE) were also associated with these outcomes in girls, p, p ′-DDE was no longer associated in multi-pollutant models with BKMR. The pyrethroid metabolites cis -(2, 2-dibromovinyl)-2, 2-dimethylcyclopropane-1-carboxylicacid ( cis -DBCA) and trans -3-(2, 2-dichlorovinyl)-2, 2-dimethylcyclopropane carboxylic acid ( trans -DCCA) were inversely related to BMI-for-age and weight-for-height overall; however, results suggested that weight-for-age and weight-for-height associations for trans -DCCA (sex interaction p-valueweight-for-age  = 0.02; p-valueweight-for-height  = 0.13) and cis -DCCA (sex interaction p-valueweight-for-age  = 0.02; p-valueweight-for-height  = 0.08) were strongest and most consistent in boys relative to girls. BKMR also revealed joint effects from the chemical mixture. For instance, with increased concentrations of p, p ′-DDE, the negative exposure-response relationship for cis -DBCA on BMI-for-age became steeper. Conclusions: Our single-pollutant and multi-pollutant model results show that maternal serum p, p ′-DDT concentration was consistently and positively associated with body composition and body weight in young girls and that maternal urinary pyrethroid metabolite concentrations (particularly cis -DBCA and trans -DCCA) were negatively associated with body weight and body composition in young boys. Joint effects of the insecticide exposure mixture were also apparent, underscoring the importance of using advanced statistical methods to examine the health effects of chemical mixtures. Highlights: p, p ′-DDT was associated with higher body composition in girls only. Pyrethroid metabolites were associated with lower body composition in boys. Insecticide exposure associations were influenced by the overall exposure mixture.